Design of Automatic Feeder with Adjustable Temperature, PH, and Weather for Catfish - Pebri Antara; Ema Utami; Kusnawi Kusnawi (Cerdika: Jurnal Ilmiah Indonesia, 2025)
This study aims to analyze the influence of service quality, tax collection strategies, and tax sanctions on taxpayer compliance in paying Land and Building Tax (PBB-P2) in Bekasi City. Data were collected through questionnaires distributed to 60 land and building taxpayers. The study employed multiple linear regression analysis using SPSS version 27 to process the data. The results showed that service quality had a positive and significant effect on taxpayer compliance, with a t-value of 2.083 greater than the t-table value of 2.002. Conversely, the tax collection strategy showed a t-value of 0.649, which is less than the t-table value, indicating no significant effect on taxpayer compliance. Meanwhile, tax sanctions had a t-value of 6.577, exceeding the t-table value, demonstrating a significant positive impact on compliance. Additionally, the F-test resulted in a value of 32.519, suggesting that when analyzed simultaneously, service quality, tax collection strategies, and tax sanctions collectively have a positive influence on taxpayer compliance. These findings highlight the importance of effective service delivery and enforcement mechanisms to enhance tax compliance for PBB-P2 in Bekasi City